ANALISA KINEMATIK SESAR PALU-KORO SEGMEN PALU DAERAH WISOLO HINGGA WERA KABUPATEN SIGI PROVINSI SULAWESI TENGAH - Harly Hamad (Jurnal Sains dan Teknologi Tadulako, 2021)
The Sulawesi Island is composed of a complex tectonic arrangement, one of the reasons for the complexity of the tectonic arrangement in Central Sulawesi, namely the presence of the Palu-Koro Fault (Bellier, et al. 2001). This research discussed the tectonic evolution and kinematics of the Palu Koro fault in the Palu segment from Wisolo to Wera, Sigi District, Central Sulawesi Province and its surroundings, to describe the succession of paleostress fields, 150 striations in the fault plane were measured in 5 paths of the measurement location. The stress inversion method developed by Delvaux and Sperner (2003) used in analyzing the stress regime to determine the evolution of stresses that developed in the research area using the Win Tensor 5.0.1 application. The results of rock deformation stress inversion analysis shows the order of 4 orientations of the elongation axis, namely in the first phase with the Southwest – Northeast orientation, the second phase with the South – North orientation, the third phase with the North West – South Southeast orientation, and finally the fourth phase with the Northwest – Southeast orientation. Based on the results of the reconstruction, the Palu-Koro Fault in the Palu segment from the Wisolo to Wera area was formed in the first phase with a downward or oblique movement on the Southwest – Northeast elongation axis and the Northwest – Southeast stress orientation with the stress regime type, namely strike slip